Understanding Military Pedagogy. (13th May 2015) - Juhary, Jowati
Abstract: There are not many military tertiary institutions in the world. The famous military tertiary education providers include the ones located in the United States such as the United States Military Academy (West Point) and the United States Naval Academy; the Royal Military Academy Sandhurst, United Kingdom; the Special Military School of St Cyr, France; and PLA National Defence University, China. In fact, each country owns at least one higher education provider for its future defenders. In Malaysia, the National Defence University of Malaysia (NDUM) is the sole provider of education at tertiary level for future military personnel. In comparison to other higher learning institutions, not many writings are done on military education and pedagogy. As such the learning environment and experience becomes such an interesting idea to be studied. This paper aims at discussing the concept of military pedagogy, which is argued to be the basis of teaching and learning at these military tertiary institutions. As a concept paper, the arguments revolve around the importance of military pedagogy, its similarities and differences with the normal pedagogy as a whole and the implementations of military pedagogy at the NDUM. The paper concludes the discussion with what may constitute military pedagogy at the NDUM that can help to enrich students' learning experiences.